OP0013 A Novel Pro-Inflammatory B Cell Population Infiltrating the Rheumatoid Synovium can be Identified by Expression of FCRL4. (23rd January 2014) - Yeo, L.; Lom, H.; Buckley, C.; Filer, A.; Raza, K.; Scheel-Toellner, D.
Abstract : Background: The importance of the B cell lineage in RA pathogenesis is highlighted by the clinical effectiveness of rituximab. Potential mechanisms by which B cells drive disease processes in RA include their ability to produce autoantibodies, act as antigen-presenting cells, or secrete cytokines. Our recent findings suggest a pro-inflammatory and destructive role for this cell type via production of cytokines including RANKL, TNF-α and IL-6 [1 ]. A memory B cell subset normally resident in epithelial niches which is characterised by expression of the inhibitory receptor FcRL4 has previously been described to express RANKL [2 ]. Objectives: As we previously made the observation that B cells in the RA synovium produce RANKL, we sought to determine whether RANKL-expressing cells belonged to the FcRL4+ B cell subset. Methods: Synovial fluid, peripheral blood and synovial tissue samples were obtained from patients fulfilling 1987 ACR criteria for RA. Mononuclear cells were isolated from synovial fluid and peripheral blood by density gradient centrifugation, stained with antibodies against CD19, CD20, CD27, IgD, CD11c, RANKL, FcRL4, CD95 and CD21, and analysed by flow cytometry. Mononuclear synovial fluid cells were stained with antibodies against CD19 and FcRL4 and sorted using a Mo-Flo™ cell sorter. Taqman™ microfluidic cards were used to detect mRNA expression of 48 cytokines by real-time PCR in these samples. Immunofluorescence staining was performed on 5 µm frozen tissue sections with antibodies against CD20, RANKL and FcRL4. Results: FcRL4-expressing B cells, comprising 4-22% of the B cell population, were detected in the synovial fluid at a significantly higher frequency compared to matched peripheral blood (n=12, p=0.0004). RANKL was significantly enriched in the FcRL4+ B cell population compared to the FcRL4- population (p=0.006). Both FcRL4+ B cells and RANKL+ B cells were predominantly switched IgD-CD27+/- memory B cells, expressing significantly higher levels of CD11c and CD95, and lower CD21 levels than the FcRL4- or the RANKL- population. FcRL4+ B cells expressing RANKL were also present in synovial tissue (n=4). At the mRNA level, sorted FcRL4+ B cells were found to express considerably higher levels of both RANKL and TNF compared to the FcRL4- fraction (n=5). Conclusions: We have identified a novel subset of B cells in the RA synovium which is characterised by expression of FcRL4 and has not previously been described in RA or any other chronic inflammatory joint condition. FcRL4+ B cells produce RANKL, and express high levels of TNF mRNA, indicating a destructive, pro-inflammatory role for this B cell subpopulation in RA pathogenesis. References: Yeo L, Toellner KM, Salmon M, Filer A, Buckley CD, Raza K, Scheel-Toellner D: Cytokine mRNA profiling identifies B cells as a major source of RANKL in rheumatoid arthritis . Ann Rheum Dis 2011, 70 (11):2022-2028. Ehrhardt GR, Hsu JT, Gartland L, Leu CM, Zhang S, Davis RS, Cooper MD: Expression of the immunoregulatory molecule FcRH4 defines a distinctive tissue-based population of memory B cells . J Exp Med 2005, 202 (6):783-791. Acknowledgements: The University of Birmingham has filed a patent on the subject of this work. Disclosure of Interest: None Declared